Notes on the sun dance of the Sarsi. Anthropological papers of the AMNH - Goddard, Pliny Earle, 1869-1928.; Skinner, Alanson, 1886-1925.; Wallis, Wilson D. (Wilson Dallam), 1886-1970. (New York : Published by order of the Trustees, The American Museum of Natural History, 1919)
p. 271-385 : ill. 25 cm. Includes bibliographical references.